The power of the European Parliament in cooperation legislative procedure - Lučić Sonja (Međunarodni Problemi, 2004)
The author explores the power of the European Parliament (EP) in the co-operation procedure, using health and safety Directives as a sample. The measure of power is success of the amendment. Each amendment proposed by the EP was traced through the legislative process, coded according to its type proportion adopted and its reading was introduced in. The results demonstrate that the EP is an influential legislator, as a large proportion of EP amendments is incorporated into the final legislative text. As for the factors affecting the success of amendments the analysis finds that the role of the Commission is considerable, that less politically controversial amendments are more often accepted, but non-technical amendments have a high acceptance rate as well, and that amendments introduced in the second reading have a lesser chance of success than those proposed in the first reading.